Research on the Impact and Countermeasures of Exhibition Environment on Hotel Indoors - Fu, Shibo (Transactions on Social Science, Education and Humanities Research, 2024)
In the modern hotel industry, the optimization of indoor display environment not only affects the first impression of customers, but also has a profound impact on the brand image and market competitiveness of the entire hotel. A well-designed display can significantly enhance customer experience, enhance customer satisfaction and loyalty towards the hotel. The focus of this study is to explore the overall impact of display environment on the indoor atmosphere of hotels, and provide targeted improvement strategies. Further empirical research is used to support theoretical analysis and strengthen the practical application value of display environment. The article aims to provide hotel managers with a systematic solution to optimize indoor displays and stimulate the potential commercial value of the hotel.